Plasma polymerization of hexamethyldisiloxane: Revisited. Issue 2 (28th September 2020) - Hegemann, Dirk; Bülbül, Ezgi; Hanselmann, Barbara; Schütz, Urs; Amberg, Martin; Gaiser, Sandra
Abstract: Activation reactions of molecules in plasma are investigated using plasma polymerization of hexamethyldisiloxane as a model system for plasma‐state polymerization. Underlying reaction pathways and film‐forming mechanisms are revisited based on a simplified macroscopic approach, considering the average energy available per monomer particle, E pl, in relation to the threshold energy, E th, which represents an activation barrier for plasma polymerization. Basic principles are discussed involving averaged values for collision frequency, cross‐section, and reaction rate to produce film‐forming species combining macroscopic and microscopic quantities. Considering the energy uptake from the electric field by the electrons, the energy transfer from electrons to monomer molecules, and the conversion into film‐forming species, it is demonstrated that E pl / E th is equally relevant as the electron energy distribution function for plasma‐chemical activation reactions. Abstract : Plasma polymerization using hexamethyldisiloxane as a model monomer is revisited, providing the fundamentals for a macroscopic approach based on averaged quantities. The conversion of a monomer into film‐forming species in the gas phase is governed by energy transfer, depending on electron temperature and energy invested per monomer with respect to a threshold energy observed for activation reactions.